Success factors in knowledge sharing behaviour among student bloggers - Sulaiman, Nor Intan Saniah (2013)
This paper discusses on the success factors of knowledge sharing behaviour among Malaysian undergraduate student's bloggers.Every university in the country has their own method in delivering the required knowledge to their undergraduate students, however occasionally there would still be unfulfilled requirement of students and this had not received any attention.The aim of this study is to identify the success factors for effective knowledge sharing behaviour among Malaysian undergraduate students.The study sample are student leaders in a student community representing Malaysian undergraduate students.The data collection involves investigating weblogs using content analysis approach.By analysing the data collected, the study has identified the success factors using relevant theories.The main theory used in this study is Knowledge Sharing Behaviour theory which has been adapted from four main theories. The model which identifies the success factors in knowledge sharing (KS) methods among Malaysian undergraduate students is the main contribution of this study.This research has successfully identified how Malaysian undergraduate students are using weblogs applications and other social media for knowledge sharing behaviour.